What's the fuss? Gender and academic leadership. Issue 6 (17th September 2018) - Wong, Anne; McKey, Colleen; Baxter, Pamela
Abstract : Purpose: Women continue to be disproportionately represented in top leadership positions. Leadership development programs typically focus on skills attainment. The purpose of this paper is to explore the perceptions and experiences of academic leaders in order to inform how leadership development programs may more effectively address the gender gap in leadership. Design/methodology/approach: A sequential mixed methods study design was used. Participants completed the Leadership Practice Inventory ®(LPI) survey followed by individual interviews of a subset of participants. The survey results were analyzed and compared by gender using the t -test. Thematic analysis was used to compare themes across and between genders. Quantitative and qualitative findings were integrated in the final analysis. Findings: In total, 65 leaders (38 women; 27 men) (37.7 percent response rate) participated in the survey. There were no significant demographic or statistical differences between women and men on any of the LPI® components. Five women and five men were interviewed. Thematic analysis revealed common leadership aspirations and values. Gender differences were noted in leadership attainment, mentorship and the influence of gender on leadership. While the male narratives reflected cognitive awareness of gender inequities, the female narratives also included lived experiences. Male participants focused on the importance of meritocracy whereas the female participants emphasized the gendered social and structural influences on leadership attainment. Practical implications: Leadership development programs need go beyond generic "skills-building" in order to conceptualize leadership within a gendered social context. This framework will enable critical awareness and tools for developing both women and men's fullest leadership potential. Originality/value: This study was conducted in order to better understand how academic health leaders experience the intersection of gender and leadership. The findings contribute to the current literature by providing insight into perceptual gaps that exist at the level of practice between women and men leaders. In doing so, the authors discuss how leadership development programs may play a more effective role in addressing gender equity in leadership.